Sculpting the Blender way : explore Blender's 3D sculpting workflows and latest features such as face sets, mesh filters, and the cloth brush /: explore Blender's 3D sculpting workflows and latest features such as face sets, mesh filters, and the cloth brush. (2021) - Greer, Xury
No abstract available